Analysis of the synergistic antifungal activity of everolimus and antifungal drugs against dematiaceous fungi - An, Lulu; Jia, Gengpei; Tan, Jingwen; Yang, Lianjuan; Wang, Yuemei; Li, Lei (Frontiers in Cellular and Infection Microbiology, 2023)
Chromoblastomycosis (CBM) is a form of chronic mycosis that affects the skin and mucous membranes and is caused by species of dematiaceous fungi including Exophiala spp., Phialophora spp., and Fonsecaea spp. The persistence of this disease and limitations associated with single-drug treatment have complicated efforts to adequately manage this condition. In this study, a microdilution assay was used to explore the synergistic antifungal activity of everolimus (EVL) in combination with itraconazole (ITC), voriconazole (VRC), posaconazole (POS), and amphotericin B (AMB) against a range of clinical dematiaceous fungal isolates. These analyses revealed that the EVL+POS and EVL+ITC exhibited superior in vitro synergistic efficacy, respectively inhibiting the growth of 64% (14/22) and 59% (13/22) of tested strains. In contrast, the growth of just 9% (2/22) of tested strains was inhibited by a combination of EVL+AMB, and no synergistic efficacy was observed for the combination of EVL+VRC. Overall, these findings indicate that EVL holds promise as a novel drug that can be synergistically combined with extant antifungal drugs to improve their efficacy, thereby aiding in the treatment of CBM.